Design of Microparticulated Salbutamol Sulfate PH Sensitive Pulsatile Delivery System for Chronotherapy of Nocturnal Asthma - Singh, Dr. Bhupendra (Asian Journal of Pharmaceutics (AJP), 2019)
Objective: The main objective of this study was to prepare and evaluate pH-dependent chronotherapeutic drug delivery of salbutamol using chitosan (CS) and Eudragit polymers. Materials and Methods: Chronotherapeutic microparticles were prepared in two steps, in first step core CS microparticles were prepared using glutaraldehyde cross-linking and in the second step entrapped within Eudragit S 100 and Eudragit L 100. Results: The microparticles were spherical with size ranging from 50 to 100 Î¼m. Core and coated microparticles were monodisperse (uniformity index [UI] <1.2) and had wide size distribution (UI >1.2). The Eudragit S-100 coated microparticle did not release the drug in acidic pH of the stomach, and the Eudragit S-100 and L-100 coated microparticles showed burst release at pH 7.4 and pH 5.8, indicating perfect pH sensitive pulsatile drug delivery.